Differences in efficacy and safety of pharmaceutical treatments between men and women: an umbrella review. - Gerald Gartlehner (Public Library of Science (PLoS), 2010)
Being male or female is an important determinant of risks for certain diseases, patterns of illness and life expectancy. Although differences in risks for and prognoses of several diseases have been well documented, sex-based differences in responses to pharmaceutical treatments and accompanying risks of adverse events are less clear. The objective of this umbrella review was to determine whether clinically relevant differences in efficacy and safety of commonly prescribed medications exist between men and women. We retrieved all available systematic reviews of the Oregon Drug Effectiveness Review Project published before January 2010. Two persons independently reviewed each report to identify relevant studies. We dually abstracted data from the original publications into standardized forms. We synthesized the available evidence for each drug class and rated its quality applying the GRADE (Grading of Recommendations Assessment, Development and Evaluation) approach. Findings, based on 59 studies and data of more than 250,000 patients suggested that for the majority of drugs no substantial differences in efficacy and safety exist between men and women. Some clinically important exceptions, however, were apparent: women experienced substantially lower response rates with newer antiemetics than men (45% vs. 58%; relative risk 1.49, 95% confidence interval 1.35-1.64); men had higher rates of sexual dysfunction than women while on paroxetine for major depressive disorder; women discontinued lovastatin more frequently than men because of adverse events. Overall, for the majority of drugs sex does not appear to be a factor that has to be taken into consideration when choosing a drug treatment. The available body of evidence, however, was limited in quality and quantity, confining the range and certainty of our conclusions.